A Listeria monocytogenes clone in human breast milk associated with severe acute malnutrition in West Africa: A multicentric case-controlled study - (:unkn) unknown (My University, 2021)
Severe acute malnutrition (SAM) is a major public health problem affecting children under the age of five in many low- and middle-income countries, and its resolution would contribute towards achieving the several sustainable development goals. The etiology of SAM is pluri-factorial, including delayed maturation of the gut microbiota, suboptimal feeding practices and dysfunctional breastfeeding. The recent serendipitous detection of Listeria monocytogenes in the breast milk of Malian women, in contrast to French women, suggests a possible association with SAM. Methodology/ Principal findings To investigate the possible association of L . monocytogenes carriage in breast milk and SAM, a case-control study was performed in Senegal, with subjects recruited from two areas. Using 16S amplicon sequencing, a culture independent method, 100% (152/152) of the mothers were positive for L . monocytogenes in their breast milk while qPCR analysis gave lower recovery rates. Interestingly, after enrichment in Fraser broth and seeding on PALCALM agar, all 10 isolated strains were isolated from the milk of 10 mothers who had SAM children which also had a significantly increased relative abundance of L . monocytogenes (0.34 (SD 0.35) vs 0.05 (SD 0.07) in controls, p<0.0001). The high genomic similarity between these strains and Malian breast milk strains from a previous study supports the hypothesis of endemic clone carriage in West Africa. Moreover, the in vitro growth inhibition of L . monocytogenes using breast milk samples was obtained from only 50% of the milk of mothers who had SAM children, in contrast to control samples which systematically inhibited the growth of L . monocytogenes with a higher inhibition diameter (15.7 mm (SD 2.3) in controls versus 3.5 mm (SD 4.6) in SAM, p = 0.0001). Lactobacillus and Streptococcus isolated from the breast milk of controls inhibit L . monocytogenes in a species-dependent manner. Conclusions/Significance Our study reve
Keywords: African Research